Macrobending Multimode Plastic Optical Fiber Coated with PANI-PVA composite as a pH sensor - Rohedi, Ali Yunus; Ainun, Rizqi Nur; Fatimah, Iim; Puspitasari, Nurrisma; Sudarsono, S; Yudoyono, Gatut (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, LPPM-ITS, 2024)
The measurement of pH is very important in the medical, industrial and research worlds and each requires measuring instruments with different sensitivities.Measuring the pH of a solution in principle measures hydrogen ions in a solution.In this research, a pH sensor was designed and fabricated using multimode fiber optic macrobending with the fiber optic cladding being peeled off and replaced with a PAni-PVA (polyaniline-polyvinyl alcohol) composite layer.The bending diameter of plastic fiber optics is varied with sizes d = 2.5 cm, d = 2 cm, and d = 1.5 cm.The test results show that the pH sensor created is capable of measuring the pH of the solution linearly in the range pH = 2 to 10 <w:LsdException Locked=